Characteristics of Modified Spiral Thrust Bearing through Geometries and Dimension Modifications - Mohd Danial Ibrahim (Japanese Society of Tribologists, 2018)
This research focuses on the optimum design of fluid dynamic bearing (FDB) named modified spiral design. The objective is to improve the pressure and velocity distribution inside the FDB. In this paper, the current spiral design has 12 number of grooves while the modified spiral design has 24 number of grooves. Both design can be classified into two, bearing with seal and without seal. Air was chosen to replace the oil as the lubricant. Results show that the modified spiral bearing design has comparable characteristics compared to conventional spiral design in terms of pressure and velocity distribution. Modified spiral geometries also shows a tendency to replace the function of seals in FDB. This makes it possible to simplify bearing design without using any seal just by modifying its geometries based on novel modified spiral geometries. Experimental verifications also proved that the modified spiral bearing design has better air leakage control compared to the conventional ones. This phenomenon occurs in both design parameters, where when the designs are compared with respect to increase of rotational speed and air film thickness.